O ensino de leitura literária no ensino médio. - Brito, Larissa Fernandes de (Universidade Federal do Tocantins, 2022)
In this text, we reflect on the importance of literary Reading and on how it can have a productive influence in our lives. We also highlight, based on authors from the field, the role of the school is in the formation of new literary readers. These references support us in our report of an experience of conducting a literature class in a high school class, about the work Memorias Postumas de Bras Cubas, by Machado de Assis. Initially, we relied on a bibliographic study (COSSON, 2012; 2014; CÂNDIDO, 2011; COLOMER, 2007; 17) to describe our conducting experience in the context of the Pedagogical Residency, a program whose objective is to improve practical training of students in undergraduate courses.